2016
DOI: 10.1038/srep38131
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide toxicogenomics across scales: in vitro transcriptome predicts mechanisms and outcomes of exposure in vivo

Abstract: In vitro Omics analysis (i.e. transcriptome) is suggested to predict in vivo toxicity and adverse effects in humans, although the causal link between high-throughput data and effects in vivo is not easily established. Indeed, the chemical-organism interaction can involve processes, such as adaptation, not established in cell cultures. Starting from this consideration we investigate the transcriptomic response of immortalized thyrocytes to ethylenthiourea and chlorpyrifos. In vitro data revealed specific and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Despite this limitation, in vitro toxicogenomics managed to predict modes of action with longer exposure times. Notably, interference with thyrotrope growth was the main mechanism identified (126).…”
Section: In Vitro Evidence Of Thyroid Disruptionmentioning
confidence: 99%
“…Despite this limitation, in vitro toxicogenomics managed to predict modes of action with longer exposure times. Notably, interference with thyrotrope growth was the main mechanism identified (126).…”
Section: In Vitro Evidence Of Thyroid Disruptionmentioning
confidence: 99%
“…Contrastingly, recent studies have shown that, after repeated CPF treatment, the mice seemed to develop some tolerance to CPF-induced effects, suggesting that the detoxifying mechanisms are possibly involved in the induction of tolerance. Compensatory mechanisms were not active in thyroids of mice treated with the same CPF concentrations [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to evaluate the effects of a chronical exposure to the environmental detected concentrations of CPF in mice exposed in utero and postnatally to the pesticide. The pregnant females were fed for all the pregnancy and the nursing period [ 24 ] with three different concentrations of CPF (0.1 mg/kg/day, 1 mg/kg/day, 10 mg/kg/day), that are commonly found in fruits and vegetables. Afterwards, weaned mice were fed in the same manner until the time of sacrifice.…”
Section: Introductionmentioning
confidence: 99%
“…RNAseq experiments were previously conducted on PCCL3 cell line and have been already described, also reporting details on cluster building approach [32].…”
Section: Methodsmentioning
confidence: 99%